Effects of Irradiance and Cutting Interval on Growth, Yield, Persistence and Nutritive Value of Asystasia Intrusa - Mokhtar, Suparjo Noordin (2008)
Asystasia intrusa, a species introduced 90 years ago, is now a naturalized weed in Malaysia that is prevalent under oil palm plantations. However, this species is known to be very palatable to cattle and goats. Despite being recognized as a shade plant, its response to shade has not been studied. Similarly, the appropriate cutting interval for optimum yield and quality has not been determined. A study was, therefore, conducted to determine the performance of animals consuming A. intrusa and the effects of shading and cutting interval on its yield, chemical composition, growth and persistence. Experiments were conducted encompassing the; i) intake and nutritive value of A. intrusa in herbivores when harvested from the field; ii) effects of cutting interval and shade levels on yield, growth, persistence of survival, chemical composition, in vitro dry matter digestibility (IVDMD), essential amino acid (EAA) and mineral concentrations of A. intrusa grown in a glasshouse; and iii) optimum light requirements for photosynthesis. Asystasia intrusa is very palatable and nutritious for ruminant and non-ruminant herbivores. Adult rams consumed A. intrusa dry matter (DM) at a rate of 33 g kg-1 body weight. Both acid detergent fiber (ADF) and neutral detergent fiber (NDF) were digested at a rate of 590 g kg-1 DM. The digestible energy (DE) and dry matter digestibility (DMD) were 2.1 mcal kg-1 DM and 620 g kg-1 DM, respectively. In rabbits, the DE and DMD value in this experiment was 2.2 mcal kg-1 DM and 509 g kg-1 DM, respectively. The mean IVDMD was 612 g kg-1 DM for leaf and 451 g kg-1 DM for stem which was within the normal digestibility of most forages. The digestibility of CP was quite low with 496 g kg-1 CP in rabbits and 500 g kg-1 CP for rams. As a result, A. intrusa had DCP of 68 g kg-1 DM in rams and 101 g kg-1 DM in rabbits. The CP concentration in leaf, stem and aerial part was 326, 167, and 253 g kg-1 DM, respectively. Both cutting interval and shade had an effect on the crude protein (CP) concentration. Crude protein in leaf decreased from 354 g kg-1 DM at 4 week cutting interval to 303 g kg-1 DM at 12 weeks. In stem, CP concentration of young A. intrusa was 213 g kg-1 DM which declined to 144 g kg-1 DM at longer cutting interval. They showed no difference between 8 and 12 week-cutting interval. On the other hand, with increased shading, the leaf CP concentration increased from 278 g kg-1 DM in the open to 361 g kg-1 DM at 93% shade. Shade has no effect on the CP concentration of stem.An essential amino acid profile of leaves showed that cystine concentration decreased with higher shade levels, while histidine increased with longer cutting interval. The most limiting EAA were histidine, lysine and methionine in leaf, and histidine and methionine in stem. Lysine concentration of stem was higher than leaf, especially when cut early. Essential amino acid constituted 35.2% of the leaf CP, and 37.7% of stem CP. Mineral concentrations increased with more shade and longer cutting interval in leaf and stem, except for Mg in leaf. Similarly, the P concentration in leaf increased with age. The ratio of Ca:P was 4.3 in leaf and 5.9 in stem, thus formulation of ration for calcium would be made easier. The concentration of fiber in A. intrusa was low relative to other tropical forages. The concentration of ADF in leaf, stem and aerial parts of A. intrusa were 158, 393 and 258 g kg-1 DM, respectively. Neutral detergent fiber in leaf, stem and aerial parts were 463, 536 and 494 g kg-1 DM, respectively. The ADF, as well as NDF, was highest with long cutting interval in both leaf and stem. They showed no difference in concentrations between 8 and 12 week cutting interval. Shading had contrasting effects on ADF and NDF and on leaf and stem. In the leaf, the ADF decreased while the NDF increased with increasing shade. In contrast, stem ADF increased as shade increased. The photosynthetic rate of A. intrusa increased when incident light was increased from 59 μmol photons m-1 s-1 to a peak at 600 μmol photons m-1 s-1 after which it declined. This shows that it is a shade plant with sun tolerant property. The light compensation point for A. intrusa occurred at 81.2 μΜοl photons m-2 s-1. The water use efficiency of A. intrusa was 1.46. The efficiency of A. intrusa to convert solar energy to chemical energy was 0.018. Shade and cutting intervals affected the morphology and growth of A. intrusa. Increasing shade reduced the number of branches and nodes. Plant was shorter (15.5 cm) in the open than in heavy shade (27.0 cm). They flower at all height, with shorter plants tending to have more flowers. In contrast to flower, seed production of A. intrusa was higher in taller plants. Canopy size and leafiness was influenced more by cutting interval than by shade. The cumulative annual yield of leaf was only affected by shade, while in stem, both cutting interval and shade affected the annual yield.